PENERAPAN APLIKASI KAMUS EKONOMI SYARI’AH BERBASIS ANDROID STUDI KASUS DI FAKULTAS EKONOMI DAN BISNIS ISLAM UIN AR-RANIRY BANDA ACEH - Haji Putra; Hendri Ahmadian (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2018)
Dictionary is what is needed to find a term with the right translation. Current technological developments make things very easy and inexpensive. The use of smartphone technology is now very suitable to replace the printed dictionary into a digital dictionary. This study aims to provide convenience for users who want to find the meaning of the term syari'ah especially for students of the Islamic Economics Study Program of the Faculty of Economics and Islamic Business, Ar-Raniry State Islamic University, Banda Aceh. This research uses Research and Development (R&D) method and is supported by the waterfall method for system development. Based on the question number 10 in this study, the conclusion of the respondents is only 2% which states neutral from all respondents, it can be said that almost all respondents said the application of Islamic Economics Dictionary makes it easier in the search for shari'a economic terms rather than dictionary shaped print.